Tax incentives and Malaysian SMEs performance: a mixed method approach / Nadiah Abd Hamid - Abd Hamid, Nadiah (Institute of Graduate Studies, UiTM, 2015)
Governments around the world have implemented several tax policies to strengthen the competitiveness and investment capacities of the small and medium-sized enterprises (SMEs) specifically, those in the manufacturing sector. In Malaysia, the importance of SMEs in industrialization and economy has led the government to extend tax incentives to eligible SMEs. Successful utilization of tax incentives willenable SMEs to reduce the cost of doing business through deductible tax exemptions. Unfortunately, not many SMEs have been successful in utilizing the granted tax incentives. Hence, the goal of this study is to investigate the performance of Malaysia“s SMEs in manufacturing sector which have been granted tax incentives. Specifically, this study identifies the factors leading to the successful utilization of tax incentives from the SMEs owners“/managers“ perspectives, analyses the financial characteristics differences between successful and unsuccessful SMEs“ utilization of tax incentives and determines the relationship between the financial characteristics, age of the company and tax incentives on SMEs performance. Two methodological approaches for data collection were employed; questionnaire survey and financial statements analysis. For the survey, factor analysis was applied to analyze the key factors leading to successful utilization of tax incentives and the analysis was further extended using Logistic Regression. Discriminant analysis was used to differentiate the financial characteristics between successful and unsuccessful SMEs where the tax exempt income account reported in the financial statements stands as proxy in differentiating both categories of SMEs…